Nível de atividade física e fatores associados em idosos residentes no município de Maceió - Mourão, Ana Raquel de Carvalho [UNIFESP] (2011)
The fast and intense aging of the population in Brazil and in the world seems to be a consequence of a better level of health that happens during certain phases of the existence. However, the necessity to keep the autonomy and the independence of the aged ones has a pertinent relation with their levels of physical activity. Aim: to analyse and identify the level of physical activity and associated factors, in special in the domain of the transports and leisure activities of the aged residents in the urban zone of Maceió. Methods: The applied methodology is the transverse delineation, in a population base, with a sample of 319 old people, 97 men and 222 women, the average age was 69,24 years (± 7.12 years). With a minimum value of 60 years and the maximum one of 92 years old. For evaluation of the physical activity, in special in the domain of transport and leisure, it was applied the "International Questionnaire of Physical Activity" in its long version, with the cutoff point in 150 minutes/week and for evaluation of the health, it was used the Health Scale of De Vitta (2001). The data was analysed through descriptive analysis, Fisher test and analysis of multiple regression of the predominance reason, being the level of signification adopted p <0,05. Results: 87,5% of the old people researched were classified as insufficiently active in the transport area and 76.2% were considered insufficiently in the leisure area. The physical activity in the transport, was considered insufficient, but was significant among the elders with more advanced ages, due to higher schooling and it was considered dissatisfied in the physical health, compared in the analysis, adjusted in the two models (demographic model; demographic model / perceived health). In the leisure area, the physical activity done in an insufficient form was significant among women, with advanced age, in the elders with less per capita income, while reporting the compared physical health and the auto perception of the mental health it was dissatisfied in the two adjusted models. Conclusion: the results of this study point to a high predominance of insufficiently active elders in the transport activity and in the leisure time. This study favors the achievement of new researches, with the purpose of identify the possible personal or environmental barriers for practicing the physical activity, with consequent promotion of physical activity for the elders of Maceió.